“No End Point Detected”: A Unique Coagulation Profile Unmasking Dysfibrinogenemia - Kelsey Uminski; Xiu Yan Jiang (Case Reports in Hematology, 2025)
Dysfibrinogenemia is a rare qualitative fibrinogen disorder that can present with bleeding, thrombosis, or both. We report a case of a young woman with first-trimester pregnancy loss and severe hemorrhage, whose coagulation tests reported “no end point detected” on PT, PTT, and Clauss fibrinogen assays. This pattern should prompt consideration of profound hypofibrinogenemia or qualitative fibrinogen defects. Fibrinogen replacement normalized PT and PTT and yielded measurable fibrinogen levels, enabling definitive diagnosis. Discordant activity and antigen levels, along with a pathogenic FGB variant, confirmed dysfibrinogenemia. This case underscores the importance of considering fibrinogen disorders in uninterpretable coagulation profiles and initiating early replacement.